Status and distribution of Rhesus Macaque, Macaca mulatta in metropolitan Dhaka City (Journal of the Asiatic Society of Bangladesh, Science, 2013)
A field study was conducted on the status and distribution of the population of rhesus macaque, Macaca mulatta (monkeys) between June 2005 to September 2005. The population survey was made in 10 study sites of old Dhaka city employing transect census technique. I found a total of 178 rhesus macaques ranging in 10 individual troops in old part of Dhaka city. A good number of rhesus population was noted in three places, among them the highest population was seen in Shadhana Awshadhalaya Factory area (59 individuals) and the lowest was (4 individuals) in Radhika Mohan Bosak lane. Population study of rhesus macaques and investigation of their distribution is extremely important as they become part of the ecosystem of those areas. Hence, appropriate conservation measures should be taken to protect the monkeys. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15606 J. Asiat. Soc. Bangladesh, Sci. 38(2): 175-181, December 2012